Global coordination and challenges of technical standards and application specifications for marine clean alternative fuels in the IMO’s new emission reduction regulations - Wang, Shasha; Liu, Yanan; Zhang, Jinglin; Zhao, Lifang; Liu, Xiaofei (Frontiers in Marine Science, 2025)
IntroductionAgainst the backdrop of intensifying climate change, new emission reduction regulations from the International Maritime Organization (IMO) are driving the shipping industry to accelerate decarbonization. Clean alternative fuels are critical for achieving net-zero emissions; however, the development of their technical standards and application specifications lags behind technological advancements. This study focuses on the standards and specifications for marine clean alternative fuels under IMO’s new regulatory framework, aiming to address global coordination challenges and support the green transition of the shipping industry.Methods​This research employs a multidimensional approach: systematically reviewing policies and regulations from the IMO and major shipping nations/regions; integrating authoritative data from sources such as DNV GL and Clarksons Research to conduct a life-cycle assessment of mainstream clean alternative fuels; and constructing three representative scenarios through scenario analysis to evaluate fuel competitiveness and the direction of standard development.Results​The analysis reveals significant disparities in regulatory frameworks: China’s "1+N" policy system emphasizes top-down coordination, the EU relies on carbon trading mechanisms and mandatory measures like FuelEU Maritime, Japan prioritizes safety standards (e.g., ClassNK guidelines), and Singapore adopts pragmatic policies to establish a green fuel hub. Three major challenges in global standard harmonization are identified: geopolitical competition leading to fragmentation of standards, technological innovation outpacing regulatory development, and uneven infrastructure deployment.DiscussionTo address these challenges, this study proposes establishing a global multi-level governance system, accelerating the construction of port infrastructure, and promoting the integration of international policies and standards. These measures aim to facilitate the coordinated development of technical standards and application specifications for marine clean alternative fuels, providing a systematic foundation for the industry’s green transition.